The Effectiveness of Internal Audit in Regional Public Hospitals as Regional Public Service Agencies - Septo Pawelas Arso; Antono Suryo Putro (Jurnal Manajemen Kesehatan Indonesia, 2022)
Public hospitals as mandated by regulation, managed as a public service agency, which given the flexibility on financial and resources management to perform good business practices in order to improve community services. As a public enterprise, regional hospitals must conduct good corporate governance by optimizing resources and providing quality services. The internal audit function have important role in this area. The purpose of this study was to determine the effectiveness of the implementation of internal audit in regional public hospitals as public service agencies. The research method was descriptive with qualitative approach. Research data was collected by observation of documents and in-depth interviews in 2 hospital, regional public hospital in district and regional public hospital at Central Java Province. The research subjects consisted of directors, Internal Auditor Unit ( SPI), service department, , finance and general affair. Data was processed and then content analyzed.  Based on the research, internal audit unit structure were just formed to fully regulations. The internal audit team were incompetent, no training, job descriptions of staff had not been detailed and auditor team was double job as additional task. Audit function was more focused on the compliance of financial aspects and accountability. The function of performance evaluation and compliance on regulations had not been carried out. The constraints are the limited number of personnel and double jobs. Hospital directors were usually immediately aware of problems that arise even without reports from the internal audit unit. Monitoring and evaluation of internal audit unit has not been carried out intensively. Internal audit function had not been effectively performed. It is need to appoint staff with appropriate competencies, the role and function of the internal audit unit have to be improved through the establishment of specific job descriptions and the granting of broader authority to audit in all units.